Development of a genomics-based LAMP (Loop-Mediated Isothermal Amplification) assay for detection of Pseudomonas fuscovaginae from rice - Ash, Gavin J.; Lang, Jillian M.; Triplett, Lindsay R.; Stodart, Benjamin J.; Verdier, Valérie; Vera Cruz, Casiana; Rott, Philippe; Leach, Jan E. (Scientific Societies, 2014)
The vast amount of data available through next-generation sequencing technology is facilitating the design of diagnostic marker systems. This study reports the use of draft genome sequences from the bacterial plant pathogen Pseudomonas fuscovaginae, the cause of sheath brown rot of rice, to describe the genetic diversity within a worldwide collection of strains representing the species. Based on a comparative analysis with the draft sequences, primers for a loop-mediated isothermal amplification (LAMP) assay were developed to identify P. fuscovaginae. The assay reported here reliably differentiated strains of P. fuscovaginae isolated from rice from a range of other bacteria that are commonly isolated from rice and other plants using a primer combination designated Pf8. The LAMP assay identified P. fuscovaginae purified DNA, live or heat-killed cells from pure cultures, and detected the bacterium in extracts or exudates from infected host plant material. The P. fuscovaginae LAMP assay is a suitable diagnostic tool for the glasshouse and laboratory and could be further developed for in-field surveys.